Experimental Measurement of Particle Velocity in a High Reynolds Micro-channel Flow - Choi, Jongin; Jung, Sunghwan (Biochip journal, 2020)
The present work is to provide experimental measurements of particle velocity in a microchannel flow at the Reynolds number of 10 and their respective particle positions in the channel where the velocities were measured. The particle position measurements which includes their depths were realized without an intricate optical set-up by controlling the particle path with multiple flow rates. The experimental measurements of particle velocity combined with the position measurements were subsequently used to confirm accuracy of particle velocities numerically estimated by a flow simulation exclusive of particle migration. The numerical estimates and experimental measurements of particle velocity agree with a difference of only less than 5%. The agreement was also supported by a detailed quantification.